The rate of cholangiocarcinoma in Caroli Disease A German multicenter study. Issue 2 (February 2022) - Fard-Aghaie, Mohammad H.; Makridis, Georgios; Reese, Tim; Feyerabend, Bernd; Wagner, Kim C.; Schnitzbauer, Andreas; Bechstein, Wolf O.; Oldhafer, Felix; Kleine, Moritz; Klempnauer, Jürgen; Rolinger, Jens; Nadalin, Silvio; et al.
Abstract: Background: Caroli Disease (CD) and Caroli Syndrome (CS) are rare disorders presenting with dilation of the intrahepatic bile ducts. CD/CS are associated with cholangiocarcinoma (CCA). However, the true incidence of CCA is still unclear, although it may serve as an indication for surgery. In this paper, we analyzed (I) the incidence of CCA in German centers, (II) reviewed our single center population together with its clinical presentation and (III) performed a thorough literature review. Methods: 17 large HPB-centers across Germany were contacted and their patients after surgical treatment due to CD/CS with histopathology were included. Medline search for all studies published in English or German literature was performed. Patients who underwent surgery at our department between 2012 and 2020 due to CD or CS were analyzed. Results: In the multicenter study, 79 patients suffered from CD and 119 patients from CS, with a total number of 198 patients. In 14 patients, CCA was found (Overall: 7, 1%; CD: 6, 3%, CS 7, 6%). Between 2012 and 2020, 1661 liver resections were performed at our department. 14 patients underwent surgery due to CD or CS. Histological examination showed synchronous cholangiocarcinoma in one patient. The literature review revealed a CCA-rate of 7, 3% in large series, whereas in case reports a rate of 6, 8% was found. Conclusion: There is risk of malignant transformation and patients with CD might also benefit from resection due to improvement of symptoms. Therefore, resection is strongly advised. As certain patients with CS require transplantation, treatment should not be guided by the relatively low rate of CCA but by the concomitant diseases that come along with hepatic failure.